Tatton-Brown-Rahman syndrome with a novel DNMT3A mutation presented severe intellectual disability and autism spectrum disorder - Yokoi, Takayuki (Hum Genome Var, 2020)
Tatton-Brown-Rahman syndrome is a congenital anomaly syndrome that manifests with overgrowth, macrocephaly, and characteristic facial features. This autosomal dominant disease is caused by a germline mutation in DNMT3A. Some patients with this syndrome develop mild to severe intellectual disability, which is sometimes accompanied by autism spectrum disorder or other developmental disorders. We report a Japanese patient with severe intellectual disability and autism spectrum disorder with a de novo mutation in the active domain of DNMT3A.